Biotic homogeneity of putative biogeographic units in the Neotropics: A test with Sapotaceae (2018)
Aim: To evaluate Morrone's (2001, Biogeografia de America Latina y el Caribe. Zaragoza, Spain: CYTED, ORCYT-UNESCO, Sociedad Entomológica Aragonesa (SEA)) Neotropical regionalization by testing the prediction that biotas are more homogeneous within than among biogeographic units. Location: Neotropics. Methods: We conducted pairwise comparisons of beta diversity of Sapotaceae species within and between biogeographic units in the hierarchical regionalization proposed by Morrone (2001, Biogeografia de America Latina y el Caribe. Zaragoza, Spain: CYTED, ORCYT-UNESCO, Sociedad Entomológica Aragonesa (SEA)), at a spatial resolution of 1-degree cells. We used a null model to control differences in sampling effort across 1-degree cells and performed beta-diversity comparisons conditional on geographic distance to control for distance decay of biotic similarity. Results: None of the biogeographic units proposed by Morrone (2001, Biogeografia de America Latina y el Caribe. Zaragoza, Spain: CYTED, ORCYT-UNESCO, Sociedad Entomológica Aragonesa (SEA)) was biotically homogeneous with respect to all other units at the same hierarchical level. This was the case even for units commonly reported to be isolated and to host distinctive taxa like “Choco.” However, five of 45 biogeographic units were biotically homogenous relative to several other units. These units were “Cuba,” “Chaco,” “Varzea,” “Cauca” and “Costa Pacífica Mexicana.” Also, beta diversity within units was often lower than beta diversity between units at relatively short geographic distances. Main conclusions: The distribution of Sapotaceae species showed generally low biotic homogeneity within Morrone's (2001, Biogeografia de America Latina y el Caribe. Zaragoza, Spain: CYTED, ORCYT-UNESCO, Sociedad Entomológica Aragonesa (SEA)) biogeographic units and did not support his biogeographic regionalization. This result suggests a strong role for dispersal and biotic interchange among biogeographic units and across barriers like the Andes. It also casts doubt on the usefulness of Morrone's (2001, Biogeografia de America Latina y el Caribe. Zaragoza, Spain: CYTED, ORCYT-UNESCO, Sociedad Entomológica Aragonesa (SEA)) biogeographic units as tools for the identification of priority areas for the conservation of biodiversity. However, relatively high biotic homogeneity within some biogeographic units suggests that they capture significant spatial patterns. In particular, noteworthy biotic homogeneity within “Cuba,” “Cauca” and “Costa Pacifica Mexicana” could be explained by isolation. Also, in “Costa Pacifica Mexicana,” patterns of biotic homogeneity could reflect closer affinities to humid lowland montane forest in Central America than to lowland rain forest in South America. Finally, substantial biotic homogeneity within “Varzea” could result from common adaptation to edaphic environments near the Amazon River. © 2018 John Wiley and Sons Ltd